Cold-tolerant and short-duration rice (Oryza sativa L.) for sustainable food security of the flash flood-prone Haor wetlands of Bangladesh - Hossain, Mobarak; Biswas, Partha; Islam, Mohammad Rafiqul (MDPI, 2023)
Rice cultivation in the low-lying basin-like wetlands, known as the Haor, is often affected by early flash floods during the first two weeks of April. The flooding is mainly caused by heavy rainfall and water surging downstream from the Meghalaya hills in India. This flash flood poses a significant threat to rice production, risking the country’s food security. Dry winter (Boro) rice is the primary food source throughout the year in the Haor region. Flash floods are the most catastrophic, affecting about 80% or even the entire rice yield. In 2017, a loss of 0.88 million metric tons of Boro rice in Haor regions cost the nation USD 450 million. To escape flash floods, it is recommended to sow Boro rice earlier, between the last week of October and the first week of November, instead of around 15 November so rice may be harvested by the last week of March before the onset of flash floods. However, early sowing has a possibility of causing grain sterility due to cold spells when the booting and heading stages of rice inevitably coincide with the cold period between 15 January and 7 February. The minimum temperature in the Haor regions ranges from 11 to 15 °C during this time. Rice is especially susceptible to low average temperatures (<20 °C) during the reproductive stage, leading to pollen abortion and the malformation of immature microspores. Low temperatures mainly impact rice cultivation in Haor regions during the reproductive phase, resulting in the degeneration of the spikelets, partial panicle exertion, and increased spikelet sterility, leading to a decrease in grain yield. Over two million hectares of Boro rice have been damaged by extreme cold spells in recent years, resulting in partial or total yield loss. To overcome the threats of flash floods and cold injury, breeding short-duration and cold-tolerant rice varieties is crucial. We assume that an economic benefit of USD 230 million per year could be achieved through the development and adoption of short-duration and cold-tolerant high-yielding rice varieties in the Haor regions of the country. In this review article, the authors summarized the problems and outline a way forward to overcome the flash flood and cold injury of Boro rice cultivation in the Haor districts of the country. Furthermore, the authors discussed the various forms and scenarios of cold damage and the global existence of cold-tolerant rice cultivars. Based on the available data from earlier research, a potential way of mitigating flash floods and cold devastation was suggested.